Pengaruh Kepemimpinan Transformasional, Lingkungan Kerja Dan Budaya Organisasi Terhadap Peningkatan Kinerja Pegawai Pada PPN Karangantu - Kurnaengsih, Kurnaengsih; Sanusi, Fauzi; Mumtazah, Liza (GEMA EKONOMI, 2023)
A person's performance can be influenced by many important factors. One of them is the extent to which the work environment and transformative leadership style affect employee performance. Good leadership is a way to improve employee performance. Effective leaders help organizations achieve their goals. Without a proper organizational culture, delivery of optimal and timely performance from every member of the organization is not possible. Therefore, organizational culture plays an important role in any company or organization. The better and stronger the organizational culture, the better the performance. The purpose of this research is to explain whether there isthe influence of transformational leadership, work environment, and organizational culture on improving employee performance at PPN Karangantu.The novelty in this study is that it has not been found in previous studies that discuss sizethe influence of transformational leadership, work environment and organizational culture on improving employee performance at PPN Karangantu. The limitations in this study are only to carry out the magnitude analysisthe influence of transformational leadership, work environment and organizational culture on improving employee performance at PPN Karangantu. The survey method is a quantitative description method (10 point evaluation) using a questionnaire supporting tool, and the sampling method is based on simple random sampling. The number of samples used to test the three identified hypotheses was 65 people.The results showed that the influence of transformational leadership, work environment, and organizational culture on improving employee performance at Karangantu PPN showed a significant positive effect between transformational leadership, work environment, and organizational culture on employee performance. We show that the most important variable affecting employee performance at PPN Karangantu is organizational culture (X3). This is because the organizational culture variable (X3) has the largest regression coefficient value compared to the change leadership (X1) and work environment (X2) variables, and the three hypotheses are positive and significant. That proves something. affected value.